2018
DOI: 10.1212/wnl.0000000000005853
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord volume loss

Abstract: SCV loss over time relates to the number of clinical relapses in RRMS, but overall does not differ between RRMS and SPMS. SCV proved to be a strong predictor of physical disability and disease progression, indicating that SCV may be a suitable marker for monitoring disease activity and severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 33 publications
(63 reference statements)
1
31
0
1
Order By: Relevance
“…As such, obtaining spinal cord atrophy measurements from brain scans could represent a viable, efficient and clinically meaningful alternative to the more technically challenging spinal cord image acquisition, in particular in multi-centre settings where homogenous quality of spinal cord acquisitions is difficult to achieve. So far, the possibility to derive spinal cord measurements from brain scans has been successfully explored only in cross-sectional studies ( Prados and Barkhof, 2018 , Liu et al, 2016 , Tsagkas et al, 2018 ). In our study, notwithstanding the large variability of centres acquiring images with different expertise, protocols and field strength, we found statistically significant, but small, correlation coefficients between measurements derived from brain and cord scans, being higher for GBSI than CSA (0.3 vs 0.2), suggesting that longitudinal spinal cord atrophy from brain scans could better be derived using GBSI than using segmentation-based approaches (e.g., CSA).…”
Section: Discussionmentioning
confidence: 99%
“…As such, obtaining spinal cord atrophy measurements from brain scans could represent a viable, efficient and clinically meaningful alternative to the more technically challenging spinal cord image acquisition, in particular in multi-centre settings where homogenous quality of spinal cord acquisitions is difficult to achieve. So far, the possibility to derive spinal cord measurements from brain scans has been successfully explored only in cross-sectional studies ( Prados and Barkhof, 2018 , Liu et al, 2016 , Tsagkas et al, 2018 ). In our study, notwithstanding the large variability of centres acquiring images with different expertise, protocols and field strength, we found statistically significant, but small, correlation coefficients between measurements derived from brain and cord scans, being higher for GBSI than CSA (0.3 vs 0.2), suggesting that longitudinal spinal cord atrophy from brain scans could better be derived using GBSI than using segmentation-based approaches (e.g., CSA).…”
Section: Discussionmentioning
confidence: 99%
“…52,75,91,100102 A recent study has reported that every 1% increase in the annual rate of spinal cord volume loss is associated with a 28% risk of developing disability progression in the subsequent year. 92 In a longitudinal cohort of nonspinal CIS, upper cord cross-sectional area decrease was associated with 5-year increased disability, measured by the EDSS. 52 Within the EDSS, the subscores that reflect the neurological functions mediated by spinal cord pathways, such as the pyramidal, sensory, bowel and bladder functional scores, correlated with spinal cord atrophy.…”
Section: Spinal Cord Atrophymentioning
confidence: 97%
“…73,91 A recent study has reported yearly rate of spinal cord atrophy between −0.38% in RRMS and −0.62% in SPMS. 92 A MAGNIMS multicentre study has detected a rate of −1.22% per year in patients with stable MS and −2.01% in patients who deteriorated over time. 73 Interestingly, we found a significant development of spinal cord atrophy in early PPMS patients when compared with healthy controls over only 1 year of follow up, but not in patients with established SPMS, who had a higher disability and more atrophic cord than early PPMS patients.…”
Section: Spinal Cord Atrophymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sclerosis (MS) is a chronic immune-mediated inflammatory and neurodegenerative disease that affects the central nervous system. The spinal cord (SC) is heavily affected in patients with MS and its involvement contributes substantially to disease progression (1, 2). Particularly at more advanced stages of MS, the dominant clinical manifestation of SC pathology resembles chronic progressive myelopathy (3).…”
Section: Introductionmentioning
confidence: 99%